(3JGQjN GdTGe haVGFdIs ((3YHO GdcQje Hf CMeO GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg GdChd HdG HOGjI agPg ChQGb CPcQ efgG Ef TGA Gddg JYGdi eG JjSQ GdGWdGY Ydjg hjSgd GdhUhd Edjg ef cJH GdJhGQjN s
(3BNQgG (B:s
(3hHYOg JgH QjM ef Gdjef JbHV CQhGM GdeDefjf hJbhe GdSGYI Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3eJaQbGJs